Influence of workplace wellness programs on employee productivity at listed commercial banks in Kampala, Uganda - Kivila, S. (Strathmore University, 2025)
Workplace Wellness Programs (WWPs) are pivotal in addressing organizational challenges, particularly within the banking sector, where employee productivity is a critical determinant of operational success and performance outcomes. Despite the growing adoption of WWPs globally, limited research exists on their impact in low-resource, high-pressure environments like Uganda. Uganda's banking sector faces significant pressures, with three tier-1 banks downgraded, one bank voluntarily exiting the market, and two others acquired by foreign entities. These dynamics prompted an investigation into the influence of WWPs on employee productivity within listed commercial banks in Kampala, Uganda. Guided by three specific objectives this study examined the influence of physical, mental, and social wellness interventions on employee productivity. The Biopsychosocial Theory served as the foundational framework for multi-faceted wellness interventions, complemented by the Self Determination Theory which underscored job satisfaction and motivation. The study adopted a cross-sectional descriptive survey design characterized by a quantitative research method approach. The study involved staff from listed commercial banks in Uganda and simple random sampling was employed in identifying the 337 employees from a population of 2159. The study collected primary data through an online and physical self-administered structured questionnaire. The reliability and validity scored above the minimum of 0.7 ensuring both parameters were met by the study. The study employed quantitative data analysis accomplished using statistical package for social scientists (SPSS version 27) to process mean, standard deviation, percentages, frequencies, correlation, and regressions. The findings revealed a positive and significant relationship between WWPs and employee productivity, with social wellness interventions being the strongest predictor, followed by physical and mental wellness interventions respectively. The combined predictors accounted for 31.2% of the variance in employee productivity within listed commercial banks in Kampala, Uganda. This study bridges a critical gap in understanding the role of WWPs in low-resource, high-pressure banking environments, offering new insights into how targeted wellness strategies can drive organizational success. Based on the findings, the study recommends that bank management prioritize comprehensive wellness programs, particularly those emphasizing social well-being, to enhance employee productivity. The bank staff are encouraged to participate in the various components of WWPs to maximize individual and organizational productivity. Despite its valuable contributions to academic literature and actionable insights for policymakers and industry practitioners, the study is limited by its reliance on statistical data without descriptive narratives, its focus on listed banks which have more structured and regulated environments, and the absence of longitudinal analysis to capture trends over time.
Full - text thesis